ACCURACY ASSESSMENT OF SRTM and ASTER DIGITAL ELEVATION MODELS (COVERING SOME PARTS OF SUDAN) - Awadelgeed, Awadelgeed Mohamed; AbdAlatif, Kamal; Hssan, Gamaleldeen (University of Khartoum Engineering Journal, 2022)
Digital elevation model (DEM) is a basic component of any geo-information system (GIS) and is required for many geospatial and engineering applications. Nowadays, the production of the worldwide DEMs have been improved with the use of SRTM-DEM and ASTER-DEM. Extracting topographical data by drawing contour lines from SRTM-DEM and ASTER-DEM elevation data requires accuracy assessment of SRTM-DEM and ASTER-DEM elevation data, as well as the quality of the interpolated contours to ensure its suitability for topographical mapping. This paper presents the accuracy assessment of the results obtained through conducting many tests which were performed for places with different types of topography. The overall accuracy of SRTM-DEM R.M.S.E value was found to be in the range of about ±5.873mand the overall accuracy of ASTER-DEM R.M.S.E value was found to be about ±7.411m. The study showed that further processing and improvements are conducted to remove blunders and outliers. In such cases both open global sources of elevation data (SRTM-DEM and ASTER-DEM) could be used for producing topographic maps at 1:50000 scales or less.